Model predictive fast charging control by means of a real-time discrete electrochemical model. (October 2021) - Hahn, Markus; Grüne, Lars; Plank, Christian; Katzer, Felix; Rüther, Tom; Jahn, Leonard; Danzer, Michael A.
Abstract: Model-based fast charging control of Li-ion batteries requires real-time capable models with a spatial resolution to effectively prevent metallic lithium deposition. In a recent publication we showed that a discrete electrochemical modeling approach in form of a transmission line model is able to precisely describe the dynamic behavior of electrodes in time domain. The model is able to simulate and detect local lithium deposition and fulfills the requirement of real-time capability. On this basis, we study the feasibility of nonlinear model predictive control for fast charging of a graphite electrode. For this purpose, two different approaches for the cost function are introduced. The first approach controls the anode surface potential to a target value close to 0 V vs. Li/Li +, to charge at the maximum rate and thus preventing Li deposition. The cost function can be rewritten explicitly to achieve a minimum computation time. The second approach weighs the charge current, which should be maximized, against the deposition current, which should be minimized. A trade-off between charging time and lithium deposition can be achieved allowing for varied priorities while finding the optimum charging trajectory for the targeted purpose. Highlights: Spatially distributed model of lithium-ion battery electrode. Local lithium deposition is predicted. Real-time capable optimum charge trajectory is found. Slide bar controller for trade-off between fast charging and lithium deposition. Model parameter uncertainties hardly affect the result.